"Gnawing at stone, feeding rainbows". Aquatic imagination and repatative reading of myths - Markowska, Anna (2024)
For Socrates, being possessed by the nymphs (‘nympholeptos’) meant a departure from conventionalised patterns of perceiving the world by increasing fluidity in its understanding. Although it may have seemed frightening for many people, it actu‑ally demanded gratitude for the elevation of the spirit and the heightened understanding, both wise and prophetic. Can a reparative reading of ancient beliefs and myths through aquatic imagination promote contemporary inclusive and empa‑thetic thinking? An attempt to answer this question is made by referring to water ‘nymphs’ in the Polish art and literature of the 20th and 21st centuries: Harey from Stanisław Lem’s novel Solaris, Emma Goldman appearing as a buoy on Karo‑linaFreino’s startling Confluence statue on a watery floodplain in Kaunas, and girls — the protagonists of Anna Baumgart’s film Wanda — stunned and liberated by water. In each case, the element of water supports thinking in terms of emergence, potentiality, and reparative change.
Keywords: feminism; aquatic imagination; nympholepsia; knowledge buoldigs; reparative reading; comparativism; retelling of myths